2023
DOI: 10.1007/s00520-023-07684-9
|View full text |Cite
|
Sign up to set email alerts
|

The roles of the dietitian in an 18-week telephone and mobile application nutrition intervention for upper gastrointestinal cancer: a qualitative analysis

Abstract: Purpose This study aimed to explore the patient-dietitian experience during an 18-week nutrition counselling intervention delivered using the telephone and a mobile application to people newly diagnosed with upper gastrointestinal (UGI) cancer to (1) elucidate the roles of the dietitian during intervention delivery and (2) explore unmet needs impacting nutritional intake. Methods Qualitative case study methodology was followed, whereby the case was… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…In this study, we used a mobile application and interactive platform to provide information and behavioral skills for the self-management of IBS symptoms. A recent study on a mobile nutrition counseling intervention for patients with gastric cancer reported that nutrition intervention was accompanied by professional nutrition knowledge, rapport formation, and psychological support [33]. Most of the previous studies on webbased nutrition interventions for patients with IBS have used mobile applications [7,34] but lacked the utilization of real-time interactive educational content.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we used a mobile application and interactive platform to provide information and behavioral skills for the self-management of IBS symptoms. A recent study on a mobile nutrition counseling intervention for patients with gastric cancer reported that nutrition intervention was accompanied by professional nutrition knowledge, rapport formation, and psychological support [33]. Most of the previous studies on webbased nutrition interventions for patients with IBS have used mobile applications [7,34] but lacked the utilization of real-time interactive educational content.…”
Section: Discussionmentioning
confidence: 99%